2021
DOI: 10.5194/tc-15-5041-2021
|View full text |Cite
|
Sign up to set email alerts
|

Image classification of marine-terminating outlet glaciers in Greenland using deep learning methods

Abstract: Abstract. A wealth of research has focused on elucidating the key controls on mass loss from the Greenland and Antarctic ice sheets in response to climate forcing, specifically in relation to the drivers of marine-terminating outlet glacier change. The manual methods traditionally used to monitor change in satellite imagery of marine-terminating outlet glaciers are time-consuming and can be subjective, especially where mélange exists at the terminus. Recent advances in deep learning applied to image processing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…While their code is open source, their dataset is not publicly available. A completely different approach to front delineation is taken by Marochov et al (2021). Instead of directly segmenting the entire images into the desired classes, Marochov et al (2021) use classification networks to determine the class of every single pixel in each image separately.…”
Section: Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…While their code is open source, their dataset is not publicly available. A completely different approach to front delineation is taken by Marochov et al (2021). Instead of directly segmenting the entire images into the desired classes, Marochov et al (2021) use classification networks to determine the class of every single pixel in each image separately.…”
Section: Algorithmsmentioning
confidence: 99%
“…However, this approach is no longer feasible with the rapidly growing satellite image archives, as manual delineation is a highly time-consuming, tedious, and expensive task. Recent studies (Baumhoer et al, 2019;Cheng et al, 2021;Davari et al, 2022Davari et al, , 2021Hartmann et al, 2021;Heidler et al, 2021;Holzmann et al, 2021;Marochov et al, 2021;Mohajerani et al, 2019;Periyasamy et al, 2022;Zhang et al, 2019Zhang et al, , 2021 have focused on deep learning to extract the calving front and have shown great success. However, the evaluations of these studies have generally been based on different datasets and are, therefore, not comparable.…”
Section: Introductionmentioning
confidence: 99%
“…The non-glacial area (3.63×10 5 km 2 ) is far greater than the glacial area (2297.93 km 2 ) in the THR, so the positive and negative samples are extremely unbalanced, which has negative impacts on model performance [34]. To maintain the balance of positive and negative samples as much as possible, the sub-images without glacier were removed from the samples [35], [36] and were not used in the subsequent steps. In this study, a total of 692 SCGI sub-images were retained and used for the networks and were regarded as the ground truth.…”
Section: B Data Sources and Pre-processingmentioning
confidence: 99%
“…An good example for semantic segmentation of the cryosphere with multiple classes can be found at Marochov et al (2021), in which CNNs are used for automated classification of Sentinel-2 satellite imagery in different classes. Due to the combination of RGB and near infrared data they can achieve an accuracy of over 90%.…”
Section: Related Researchmentioning
confidence: 99%